Resolving power of 2D pion interferometry - Padula, Sandra S. [UNESP]; Gyulassy, Miklos (Elsevier, 1995)
A χ2 analysis is performed to test the resolving power of two-dimensional pion interferometry using for illustration the preliminary E802 data on Si+Au at 14.6 A GeV/c. We find that the resolving power to distinguish two decoupling geometries of different dynamical models is enhanced by studying the variation of the mean χ2 per degrees of freedom with respect to the range of the analysis in the qT, qL plane. The preliminary data seem to rule out dynamical models with significant ω, η resonance formation yields.